Zoo babies - Grosvenor, Donna K. (Washington : National Geographic Society, 1978)
Portrays a variety of young animals in a zoo and shows how zoo personnel meet their needs and take care of them.
Keywords: Zoo animals -- Infancy -- Juvenile literature; Zoo animals; Animals -- Infancy